PERAN EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER DI SDN 5/33 MATTOANGIN KABUPATEN PANGKEP - Kasrawi; Mutmainnah; Hakim, Ulfayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education has become a strategic issue in elementary education amidst the challenges of globalization and technological developments, which have led to a decline in student discipline, responsibility, and cooperation. Scouting extracurricular activities are seen as an effective solution for shaping student character through direct experience and the instilling of positive values.This study aims to explore the role of Scouting extracurricular activities in student character development, particularly in the areas of discipline, responsibility, and cooperation at SDN 5/33 Mattoangin, Pangkep Regency, and to answer the question of how these activities contribute to student character development. This study employed a qualitative, descriptive approach, with data collection techniques including observation, in-depth interviews, and documentation. The data were collected using purposive sampling of teachers, Scout leaders, and students.The results indicate that Scouting activities play a significant role in improving student discipline through the habit of following rules, increasing responsibility through completing tasks and maintaining equipment, and strengthening cooperation through group activities and mutual cooperation. These findings contribute to the understanding that character education is more effective through direct experience and instilling habits in real-life situations. The conclusion of this study confirms that the Scouting extracurricular activity is an effective tool in developing students' character. Therefore, it is recommended that schools improve the quality of Scouting activities. Further research can examine broader aspects of character and use different approaches to enrich the research findings.